Multilevel Analysis of Women's Perceptions of Community‐Based Health Insurance on Healthcare Access in Sidama Region, Ethiopia: A Community‐Based Cross‐Sectional Study - Kare Chawicha Debessa; Amanuel Yoseph (Health Science Reports, 2026)
ABSTRACT Background and Aims Access to healthcare remains a major challenge in low‐ and middle‐income countries, including Ethiopia, where financial and geographic barriers limit service utilization. Community‐Based Health Insurance (CBHI) has been introduced to enhance financial protection and improve healthcare access. This study examined factors associated with women's perceptions of CBHI in improving healthcare access in the Sidama Region, Southern Ethiopia, in 2024. Methods A community‐based cross‐sectional study was conducted among women using a multistage stratified sampling approach. Data were collected through face‐to‐face interviews using the KoBoTool platform. Multilevel logistic regression analysis using Stata 18 examined individual‐ and community‐level determinants of women's perceptions of healthcare access. Adjusted odds ratios (AORs) with 95% confidence intervals were reported. Statistical significance was set at p < 0.05. Results Of 845 women sampled, 835 (98.8%) were interviewed. Women residing in low‐poverty communities had significantly higher odds of perceiving improved access compared to those in high‐poverty areas (AOR = 4.6; 95% CI: 1.8–9.1). Rural residents were less likely to report improvements than urban residents (AOR = 0.37; 95% CI: 0.18–0.68). Recent health facility visits increased positive perceptions more than fourfold (AOR = 4.1; 95% CI: 1.9–8.2), whereas missed visits reduced the likelihood by 45% (AOR = 0.55; 95% CI: 0.34–0.88). Perceived inadequacy of the CBHI package and unfair contributions were associated with substantially lower odds of positive perception. Acceptance of CBHI emerged as the strongest predictor (AOR = 6.3; 95% CI: 2.1–13.6). Conclusion Women's perceptions of CBHI are shaped by socioeconomic conditions, residence, healthcare utilization, and views on fairness and adequacy. Strengthening equitable and culturally responsive CBHI implementation may enhance healthcare access in Ethiopia and similar settings.